Rebooting TEI Pointers - Hugh A. Cayless (Journal of the Text Encoding Initiative)
The TEI Guidelines has for years contained a section on XPointer schemes which, unfortunately, has suffered from a lack of implementations. The reasons for this include the difficulty of the concepts in this section and a lack of sufficient detail in their specification. Despite this lack of use, the author feels that TEI pointers address an important set of use cases and should receive more attention. The chief advantage of TEI pointers is that they permit stand-off markup and annotation of text that is either unmarked or marked up inappropriately for the intended annotation. Their promise is a mechanism for leveraging stand-off markup and annotations of TEI documents—for example, being able to link to annotations in a document view because those annotations point to parts of the document. This paper provides some background on TEI pointers and their possible uses, and outlines the state of efforts under way to rework this section of the Guidelines by providing a more detailed specification and reference implementations.